Effect of holding pressure on microstructure and fracture behavior of low-pressure die cast A356-T6 alloy. (30th November 2017) - Wu, Xiaoyan; Yun, Ying; Zhang, Huarui; Ma, Zhen; Jia, Lina; Tao, Tongxiang; Zhang, Hu
Abstract: The effect of different holding pressures on microstructure, tensile properties and fracture behavior of A356-T6 aluminum alloy was investigated. It was observed that the ultimate strength, yield strength and elongation of A356-T6 aluminum alloy increased with the increasing of holding pressure from 85 kPa to 300 kPa. This was attributed to the finer microstructure and the elimination of porosity defects caused by high holding pressure. The fractographs of specimens obtained under lower holding pressure displayed mixed quasi-cleavage and dimple type morphology with flat dimples and large amount of porosities. However, the fractographs of specimens obtained under high holding pressure of 300 kPa clearly exhibited a dimple morphology with small and deep dimples. The differences in the tensile fracture were attributed to the different shape of eutectic Si particle and different amount of porosity defects.